Theoretical Analysis of Low-power Bidirectional Optogenetic Control of High-frequency Neural Codes with Single Spike Resolution. (21st November 2020) - Bansal, Himanshu; Gupta, Neha; Roy, Sukhdev
Graphical abstract: Highlights: Low-power and high-frequency bidirectional optogenetic control of neurons is important. The rebound effect of chloride ions and overlapping of absorption spectra affect neuronal spiking. Bidirectional control of neurons and interneurons can go upto 90 Hz and 250 Hz, respectively. Chronos-Jaws, CheRiff-Jaws, Chronos-eNpHR3.0 and vf-Chrimson-GtACR2 significantly improve performance. Study highlights the usefulness of computational optimization of stimulation protocols for optogenetic tool combinations. Abstract: Low-power and high-frequency bidirectional control of spatiotemporal patterns of neural spiking is one of the major challenges in optogenetics. A detailed theoretical analysis and optimization with ChR2-NpHR, ChR2(H134R)-eNpHR3.0, Chrimson-GtACR2 and also with prospective opsin pairs namely, Chronos-Jaws, Chronos-eNpHR3.0, CheRiff-Jaws and vf-Chrimson-GtACR2 has been presented. Biophysical circuit models of bidirectional optogenetic control in above opsin pairs expressing hippocampal neurons and fast-spiking neocortical interneurons have been formulated. The models include the important rebound effect of chloride ions and overlapping of absorption spectra. Blue light absorption by red-shifted opsins not only affects the photocurrent, but also its turn-off kinetics. Under continuous illumination, bidirectional control of spiking around 40 Hz in hippocampal neurons requires very low blue and orange light intensities of 0.014 mW/mm 2 and 0.8 mW/mm 2 with CheRiff-Jaws and 0.04 mW/mm 2, and 0.02 mW/mm 2 with Chrimson-GtACR2, respectively. Under optimal photostimulation and expression density, high-frequency limit of bidirectional control is 60 Hz and 100 Hz with ChR2-NpHR, 60 Hz and 20 Hz with ChR2(H134R)-eNpHR3.0, 90 Hz and 180 Hz with Chronos-Jaws, and 90 Hz and 250 Hz with Chronos-eNpHR3.0 in neurons and interneurons, respectively. Although, Chrimson-GtACR2 enables bidirectional control at very low-power, vf-Chrimson-GtACR2 provides control with reduced cross-talk. The theoretical analysis highlights the usefulness of computational methods to virtually optimize stimulation protocols for optogenetic tool combinations. The study is useful to generate neural codes with desired spatiotemporal resolution and to design optogenetic neuroprosthetic devices and circuits.